The European Union and the Violation of the Right to Self-determination. The Cases of Western Sahara and the Occupied Palestinian Territory - Arribas, Gloria Fernández (Polish Review of International and European Law, 2025)
Self-determination constitutes today one of the basic principles of international law. It is enshrined in the United Nations Charter and is part of the list of principles proclaimed last century in General Assembly Resolution 2625 (XXV), without a vote. The Resolution consecrated what were believed to be the essential principles to guarantee peace among states. It was adopted at specific historical time, when new states had access to the international community. These states were seeking to find their place in a world divided by an east-west confrontation which would mark international relations in the years to come.